Leigh Syndrome in an Adolescent Girl: A Case Report - Shrestha, Merina; Bajracharya, Luna; Basnet, Sudha (Journal of Institute of Medicine Nepal, 2020)
Leigh syndrome (LS) is a disorder of infancy and rarely late childhood. It presents with regression of mental and motor skills. Here, we present LS in an adolescent girl who presented with generalized dystonia and cognitive decline. Her infective, metabolic, endocrinal and autoimmune work up was normal. The neuroimaging showed progressive symmetric involvement of basal ganglia with focal intensity over bilateral lentiform nucleus and thalamic region. The cerebrospinal fluid (CSF) lactate level was elevated. Genetic test could not be performed; however the history of neuro-regression with extrapyramidal involvement with CSF and neuroimaging finding led to the diagnosis of Leigh’s syndrome.